Estudo sobre a microvascularização das pregas vocais humanas acometidas por pólipo, in vivo, através das endoscopias rígida e de contato da laringe - Cunha, Edilson Oliveira (2006)
Microvascularization of human superior membranous vocal folds tends to be parallel to the long axis. This pattern of microvascularization changes with disease. The objective this study was to describe microvascular changes in the human vocal folds with polypoid alterations as differential diagnosis with other laryngeal diseases. A retrospective study was conducted to describe alterations in the microvasculature of the vocal folds of eleven patients having polyps, who underwent laryngeal microsurgery and subsequent rigid and contact laryngoscopy. To study the microvascular changes, D Ávila (2002) classification was used. The vocal folds were divided in three regions: superior membranous, superior cartilaginous, and subglottic. The twelve types of microvessels described by D Ávila were identified in the study and 74 altered microvessels were found; dilated parallel and branching micro vessels predominated. Our findings highlight that microvascularization of the vocal folds changes with polyp formation; and the presence of branching microvessels in the surface of vocal cord lesions suggests a diagnosis of polyp formation.